(The) polar bears are pink. How (the) Germans interpret (the) definite articles in plural subject DPs - Czypionka, Anna; Kupisch, Tanja (The journal of comparative Germanic linguistics, 2019)
According to the literature, German optionally allows a definite article with generic nominals, whereas other Germanic languages require a bare nominal (e.g., English Polar bears are white). This optionality makes German different from other Germanic languages and more similar to Romance languages, in which definite articles are obligatory with generic nominals in subject positions. Since article use with generic nominals is seen as indicative of an advanced stage of grammaticalization, the question arises whether German has moved towards a more Romance-like stage of definite article use. We present judgment and reaction time data on generic statements. We ran two experiments monitoring the preferred reading of German definites in a nonlinguistic context, i.e., pictures of items showing either prototypical characteristics (e.g., white polar bears) or nonprototypical characteristics (e.g., pink polar bears). Given this nonlinguistic context, participants judged the truth value of auditorily presented sentences with different articles (i.e., These/Ø/The polar bears are white/pink). Our results show that demonstratives are interpreted as definite and bare nominals as generic. Contrary to claims in the literature, the definite article is largely interpreted as specific, following the pattern described for other Germanic languages. However, reaction times for definite articles are significantly slower than for demonstratives and bare nominals. We interpret these findings as pointing toward an ongoing change in the semantics of definite articles.